Management of Educators and Education Personnel at SDIT Taqiyya Rosyida Kartasura - Mighfar, Shokhibul; Khairun Nisa, Shifa (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
This study aims to determine the management of educators and education personnel at SDIT Taqiyya Rosyida Kartasura. This study used a descriptive qualitative method. This research will be conducted from Oct 9 to 21, 2023. Data collection through documentation, observation, and interviews. Data validation using the triangulation method by validating SDIT Taqiyya Rosyida Kartasura data. Analyze data using interactive analysis. The results showed that the management of educators and education personnel at SDIT Taqiyya Rosyida has five stages: planning, recruitment, development, evaluation, and compensation and salary deductions. Planning of educators and education personnel at SDIT Taqiyya Rosyida by analyzing the needs of educators and education personnel. In the recruitment process, the dissemination of vacancy information through social media platforms. The selection procedure starts with registration, filing, microteaching, interview, and announcement. After that, new educators intern for three months before the new school year. The development activity is called the 1-year Teachers Professional Development (TPD) program, and it is scheduled from weekly activities and different monthly materials. Meanwhile, the particular Teacher Competency Test is in September. The principal evaluates with learning supervision every three months and schedules. Compensation includes basic salaries, benefits, and additional salaries for educators who teach 24 hours a week. Payroll is also based on rank level and educator class—salary deductions for lateness, absenteeism, BPJS deductions, old age savings, social funds, etc.